Development and Pilot Implementation of a Search Protocol to Improve Patient Safety on a Psychiatric Inpatient Unit. Issue 2 (March 2017) - Abela-Dimech, Frances; Johnston, Kim; Strudwick, Gillian
Abstract : Purpose/Objective: A mental health organization in Ontario, Canada, noted an increase in unsafe items entering locked inpatient units. The purpose of this project was to develop and implement a search protocol to improve patient, staff, and visitor safety by preventing unsafe items from entering a locked inpatient unit. Description of the Project: Under the guidance of a clinical nurse specialist, an interprofessional team used the Failure Mode and Effects Analysis framework to identify what items were considered unsafe, how these unsafe items were entering the unit, and what strategies could be used to prevent these items from entering the unit. A standardized search protocol was identified as a strategy to prevent items from entering the unit. Outcome: The standardized search protocol was developed and piloted on 1 unit. To support the search protocol, an interprofessional team created a poster using a mnemonic aid to educate patients, staff, and visitors about which items could not be brought onto the unit. Educational sessions on the search protocol were provided for staff. The difference between the number of incidents before and after the implementation of the search protocol was statistically significant. Conclusions: Safety on an inpatient unit was increased as incidents of unsafe items entering the unit decreased.